2015
DOI: 10.1089/fpd.2015.2009
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Quaternary Benzo(c)phenanthridine Alkaloids Decreased Salivary Cortisol andSalmonellaShedding in Pigs After Transportation to the Slaughterhouse

Abstract: The present study was aimed at evaluating the effect of herbal extracts supplementation, particularly quaternary-benzo(c)phenanthridine alkaloids (QBA), which have been previously demonstrated to have anti-inflammatory, antimicrobial, and immune-modulator effects. We investigated the role of QBA on stress response and Salmonella shedding in finishing pigs transported to the slaughterhouse. A total of 82 pigs were orally challenged with a Salmonella cocktail (day 0) containing Salmonella Meleagridis, Hartford, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Additionally, IQAs can reduce fermentation, which also contributes to heat production, in the large intestine [ 43 ]. Elsewhere, dietary IQA’s have been demonstrated to have post-absorptive effects, such as improvements in antioxidant capacity, and also reduce cortisol concentrations following transport stress [ 16 ], supporting effects beyond the GIT. Considering these results in comparison to those of [ 38 ], who showed that only a small alkaloid proportion was absorbed, the effects of sanguinarine and other isoquinoline alkaloids beyond the GIT warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, IQAs can reduce fermentation, which also contributes to heat production, in the large intestine [ 43 ]. Elsewhere, dietary IQA’s have been demonstrated to have post-absorptive effects, such as improvements in antioxidant capacity, and also reduce cortisol concentrations following transport stress [ 16 ], supporting effects beyond the GIT. Considering these results in comparison to those of [ 38 ], who showed that only a small alkaloid proportion was absorbed, the effects of sanguinarine and other isoquinoline alkaloids beyond the GIT warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional properties as a methyl donor could contribute to a wide range of biological reactions reducing oxidative stress and methylation pathways, improving efficiency in dairy [ 13 ], meat [ 14 ] and egg production [ 15 ] from heat-stressed livestock. Plant-derived isoquinoline alkaloids such as sanguinarine reduce stress and Salmonella shedding in transported pigs [ 16 , 17 ]. Isoquinoline alkaloids inhibit cellular Na + /K + ATPases, which are important contributors to thermogenesis [ 18 , 19 ] and therefore may provide an approach to mitigate heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…In swine, Sangrovit® has been evaluated for its effects on stress response and pathogen shedding in finishing pigs [15] and ef-fects on the growth parameters in weaning piglets [3]. However, few studies have been conducted to assess the safety of MCE consumption in weaned piglets.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the extracts of M. cordata containing chelerythrine and sanguinarine were approved as the first Traditional Chinese Veterinary Medicine in feed. Products containing M. cordata extract, with a bitter flavor, have been used as a naturally-derived appetizing agent for addition to the feed of production animals including bovine ( 21 , 22 ), poultry ( 23 , 24 ), fish ( 25 ), and swine ( 26 , 27 ). With the increasing attention on food safety, it was important to study the residue of sanguinarine and chelerythrine in tissues following intragastric administration with M. cordata extracts for 3 weeks.…”
Section: Discussionmentioning
confidence: 99%